2010
DOI: 10.1111/j.1742-6723.2010.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Paediatric supracondylar humeral fractures: Emergency assessment and management

Abstract: Supracondylar humeral fractures in children are common presentations to the ED but might be challenging to both diagnose and assess clinically. The ED has a critical role in accurately assessing the child, the limb's neurovascular status and initiating treatment. A specific approach to the clinical assessment of such a child is required as failure to detect neurovascular compromise can delay appropriate treatment and result in serious consequences. Most children can be investigated with X-ray radiograph alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…One study reported 22% of nerve injuries with Grade 3 open fractures of the tibia (Beltran et al, 2012). In displaced supracondylar fractures of the humerus, nerve injuries can occur in up to 15% of patients (Allen, Hang, & Hau, 2010) and 1% in total hip arthroplasty (Schmalzried, Noordin, & Amstutz, 1997).…”
Section: Research Articlementioning
confidence: 99%
“…One study reported 22% of nerve injuries with Grade 3 open fractures of the tibia (Beltran et al, 2012). In displaced supracondylar fractures of the humerus, nerve injuries can occur in up to 15% of patients (Allen, Hang, & Hau, 2010) and 1% in total hip arthroplasty (Schmalzried, Noordin, & Amstutz, 1997).…”
Section: Research Articlementioning
confidence: 99%
“…They occur most frequently within the first decade of life, with a peak of incidence between 5 and 8 years of age [1][2][3]. This injury occurs during the time when capsule and ligaments supporting the elbow have greater tensile strength than the bone itself, which occurs during the metaphyseal remodeling that takes place during the first 10 years of development; thus, the incidence of these fractures decreases after the age of 15.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular injuries involving the brachial artery occur in 0.5% of patients [2]. Neurological injury is B10-20%, mostly affecting the anterior interosseous branch of the median nerve [1]. The ulnar and radial nerve can also be injured.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations